Chondroitin sulfate modified selenized chitosan loaded ruthenium nanoszyme, and preparation method and application thereof

CN122998401APending Publication Date: 2026-10-30南昌大学第一附属医院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611273671.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]为了弥补以上不足,本发明提供了一种硫酸软骨素修饰硒化壳聚糖负载钌纳米酶及其制备方法和应用,旨在改善现有技术面临生物利用度低、关节腔清除快、难以靶向软骨细胞及深层渗透等技术瓶颈,传统铁基纳米酶催化效率有限,且现有载体缺乏软骨靶向特异性,无法实现抗氧化与软骨修复的协同作用,壳聚糖等天然载体在中性环境中溶解性差、抗氧化能力不足,限制了其临床应用的问题

Benefits of technology

[0020]1、本发明提供的硫酸软骨素修饰硒化壳聚糖负载钌纳米酶具有优异的软骨靶向性,利用硫酸软骨素作为CD44受体的特异性配体,通过酰胺化共价修饰牢固结合于载体表面,既保留了CS与软骨细胞表面CD44受体高效结合的生物活性,又避免了物理吸附易解离的问题,显著延长药物在关节腔内的滞留时间,实现抗氧化组分向软骨细胞的精准递送。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998401A_ABST
    Figure CN122998401A_ABST
Patent Text Reader

Abstract

The application relates to the field of biological medical technology, and discloses a chondroitin sulfate modified selenium chitosan loaded ruthenium nanoscale enzyme as well as a preparation method and application thereof, which comprises a selenium chitosan carrier, a ruthenium nanoscale enzyme loaded on the selenium chitosan, and chondroitin sulfate modified on the surface of the selenium chitosan loaded ruthenium nanoscale enzyme through a covalent bond; the chondroitin sulfate is coupled through activation of carboxyl on a molecular chain and amino on a molecular chain of the selenium chitosan to form an amide bond. The chondroitin sulfate modified selenium chitosan loaded ruthenium nanoscale enzyme has excellent cartilage targeting, the specific ligand of the chondroitin sulfate is covalently modified on the surface of the carrier through amidation, the biological activity of efficient combination of CS and a cartilage cell surface CD44 receptor is retained, the problem of easy dissociation of physical adsorption is avoided, the retention time of the drug in a joint cavity is significantly prolonged, and precise delivery of an antioxidant component to cartilage cells is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical technology, and in particular to a chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme, its preparation method, and its application. Background Technology

[0002] Osteoarthritis is a degenerative joint disease characterized by cartilage destruction and degeneration. The number of patients worldwide continues to grow and is expected to reach nearly 1 billion by 2050, seriously affecting the quality of life of middle-aged and elderly people.

[0003] Currently, clinical treatment mainly uses glucosamine, nonsteroidal anti-inflammatory drugs (NSAIDs), and glucocorticoids to alleviate clinical symptoms. However, these drugs only provide symptomatic relief and cannot halt disease progression, and long-term use has significant side effects. Surgical joint replacement surgery is highly invasive and expensive, limiting patient acceptance. The pathogenesis of osteoarthritis (OA) is closely related to the imbalance of oxidative stress levels within the joint cavity. Excessive accumulation of reactive oxygen species leads to chondrocyte apoptosis, extracellular matrix degradation, and cartilage degeneration. While existing nanozyme delivery systems have shown initial success in antioxidant therapy, they still face technical bottlenecks such as low bioavailability, rapid joint cavity clearance, difficulty in targeting chondrocytes, and deep penetration. Traditional iron-based nanozymes have limited catalytic efficiency, and existing carriers lack cartilage-targeting specificity, failing to achieve a synergistic effect between antioxidant and cartilage repair. Furthermore, natural carriers such as chitosan have poor solubility and insufficient antioxidant capacity in neutral environments, limiting their clinical application.

[0004] Therefore, in response to the above problems, a chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme, its preparation method, and its application are proposed. Summary of the Invention

[0005] To overcome the above shortcomings, this invention provides a chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme, its preparation method, and its application. This aims to address the technical bottlenecks of existing technologies, such as low bioavailability, rapid joint cavity clearance, difficulty in targeting chondrocytes, and deep penetration. Traditional iron-based nanozymes have limited catalytic efficiency, and existing carriers lack cartilage-targeting specificity, failing to achieve synergistic effects of antioxidation and cartilage repair. Furthermore, natural carriers such as chitosan have poor solubility and insufficient antioxidant capacity in neutral environments, limiting their clinical application.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme comprises a selenized chitosan carrier, a ruthenium nanozyme supported on the selenized chitosan, and chondroitin sulfate covalently modified on the surface of the selenized chitosan-supported ruthenium nanozyme. The chondroitin sulfate is coupled to the amino groups on the selenized chitosan molecular chain via EDC / NHS activation to form amide bonds, thereby obtaining the chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme, denoted as SeC@Ru@CS.

[0008] As a preferred embodiment of the present invention, the ruthenium nanozyme is a ruthenium nanoparticle with a particle size of less than 20 nm, and has catalase-like, superoxide dismutase-like, and peroxidase-like activities; in the selenized chitosan, the selenium element is grafted onto the amino or hydroxyl groups of the chitosan molecular chain in the form of selenate or selenium heterocycle.

[0009] As a preferred embodiment of the present invention, the successful grafting of chondroitin sulfate is characterized as follows: the Zeta potential of the product changes from the positive potential of the selenized chitosan-loaded ruthenium nanozyme to a negative potential; an amide I absorption peak appears at 1640–1660 and an amide II absorption peak appears at 1540–1560 in the FT-IR spectrum; the grafted CS content is determined by the phenol-sulfuric acid method, the ruthenium loading is determined by ICP-MS, and the selenium content is determined by ultraviolet spectrophotometry or ICP-MS.

[0010] This invention also provides a method for preparing ruthenium nanozymes supported on selenium-modified chitosan modified with chondroitin sulfate, comprising the following steps:

[0011] Step 1: Prepare Ruthenium nanozymes RuNPs. Dissolve RuCl3·nH2O and NaAc in ethylene glycol, add PVP, transfer to a polytetrafluoroethylene-lined stainless steel autoclave and heat at 90°C for 12 h. Centrifuge to collect the precipitate, and wash three times with a mixed solvent of 70% ethanol / water to obtain RuNPs suspension.

[0012] Step 2: Prepare selenized chitosan SeC. Chitosan is fully swollen in ultrapure water, glacial acetic acid is added to form a transparent solution, sodium selenite aqueous solution is slowly added, and the reaction is carried out at room temperature for 2 h. Anhydrous ethanol is added to precipitate and wash. The precipitate is pre-frozen at -80℃ and then freeze-dried to obtain selenized chitosan SeC.

[0013] Step 3: Prepare selenized chitosan-supported ruthenium nanozyme SeC@Ru. Add RuNPs suspension to the chitosan solution swollen in step 2, stir thoroughly for 1-2 h, add glacial acetic acid to form a transparent solution, then add sodium selenite aqueous solution and react at room temperature for 2 h. Precipitate with ethanol, wash, pre-freeze at -80℃, and freeze dry to obtain SeC@Ru.

[0014] Step 4: Chondroitin sulfate carboxyl activation. Dissolve chondroitin sulfate (CS) in MES buffer, add EDC·HCl and NHS, and stir at room temperature for 20-40 min to obtain activated CS solution.

[0015] Step 5: Covalent coupling. SeC@Ru was dispersed in PBS buffer and sonicated for 5–10 min to ensure uniform dispersion. The activated CS solution obtained in Step 4 was slowly added dropwise to the SeC@Ru dispersion. The reaction was carried out at room temperature in the dark for 8–16 h, with the pH controlled at 5.5–6.0 during the reaction. After the reaction was completed, the product was collected by centrifugation, washed with deionized water, dialyzed to remove unreacted substances, and then lyophilized to obtain chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme SeC@Ru@CS.

[0016] As a preferred embodiment of the present invention, the chitosan in steps 2 and 3 is medium-viscosity chitosan with a viscosity of 200–400 mPa·s; the amount of glacial acetic acid added is 1 mL of glacial acetic acid per 50 mL of chitosan aqueous solution; the amount of sodium selenite is 1.33 g of Na2SeO3 dissolved in 1 mL of ultrapure water for every 1 g of chitosan; the mass ratio of CS, EDC·HCl and NHS in step 4 is 100:76.6:46.0; and the mass ratio of SeC@Ru to CS in step 5 is 1:1.

[0017] As a preferred embodiment of the present invention, in step 5, the centrifugation conditions are 8000-12000 rpm for 10 min, the molecular weight cutoff of the dialysis bag is 8000-14000 Da, the dialysis time is 24 h, and the water is changed every 4 h.

[0018] This invention also provides the application of chondroitin sulfate-modified selenized chitosan-loaded ruthenium nanozyme in the preparation of drugs for treating osteoarthritis or intra-articular injection formulations. The SeC@Ru@CS is reconstituted in physiological saline or PBS and administered via intra-articular injection to scavenge reactive oxygen species in the joint cavity, inhibit chondrocyte apoptosis, promote cartilage matrix synthesis, and reduce cartilage damage in osteoarthritis.

[0019] The present invention has the following beneficial effects:

[0020] 1. The chondroitin sulfate-modified selenized chitosan-loaded ruthenium nanozyme provided by this invention has excellent cartilage targeting. By using chondroitin sulfate as a specific ligand for the CD44 receptor, it is firmly bound to the carrier surface through amidation covalent modification. This not only retains the bioactivity of CS to bind efficiently to the CD44 receptor on the surface of chondrocytes, but also avoids the problem of easy dissociation due to physical adsorption. This significantly prolongs the retention time of the drug in the joint cavity and achieves precise delivery of antioxidant components to chondrocytes.

[0021] 2. The nanozyme system of this invention has multiple synergistic antioxidant and repair functions. Ruthenium nanozymes with a particle size of less than 20 nm can efficiently remove hydrogen peroxide and hydroxyl radicals in the OA microenvironment. The selenium element in selenized chitosan forms an electron transfer effect with ruthenium to maintain the active valence state of ruthenium, and synergistically exert catalase-like, superoxide dismutase-like, and peroxidase-like activities. At the same time, the degradation of chondroitin sulfate can provide raw materials for the synthesis of cartilage matrix. Chitosan gives the system good lubrication properties, realizing an integrated treatment that removes ROS, protects chondrocytes, and promotes matrix regeneration.

[0022] 3. This invention achieves directional grafting of CS onto the SeC@Ru surface through EDC / NHS covalent coupling process. The change of Zeta potential from positive to negative and the characteristic peak of FT-IR amide bond confirm the successful construction of the structure. After 8 weeks of treatment in a rat OA model, the articular cartilage surface is smooth and intact, glycosaminoglycan deposition is significantly increased, and the Mankin score of cartilage degeneration is significantly reduced, showing good prospects for clinical translational application. Attached Figure Description

[0023] Figure 1 This is a schematic diagram illustrating the preparation and characterization of RuNPs in this invention; specifically, AC: RuNPs structure under a transmission electron microscope; D: Comparison of the XRD crystal form of RuNPs with the standard card; EG: XPS diagram of RuNPs; H: Zeta diagram of RuNPs; I: Particle size analysis diagram;

[0024] Figure 2 This diagram illustrates the verification of the reactive oxygen species (ROS) scavenging function of RuNPs in this invention. Specifically, A and B: RuNPs' ability to scavenge DPPH; C and D: RuNPs' ability to scavenge O₂; E and F: RuNPs' ability to scavenge H₂O₂; G: Time-dependent verification of the H₂O₂ scavenging ability of 8 μg / mL RuNPs; H: Representative ROS staining of chondrocytes under different treatments using the DCFH-DA probe; I: Quantification of DCFH-DA probe fluorescence (ROS staining) in chondrocytes after different treatments.

[0025] Figure 3 This is a schematic diagram illustrating the biocompatibility of RuNPs of the present invention; A: Live and dead cell staining to observe the biocompatibility of RuNPs; B and C: Hemolysis test, CCK8 assay to detect the biocompatibility of RuNPs;

[0026] Figure 4 This is a schematic diagram of the SeC preparation of the present invention; A: Chitosan structure under scanning electron microscope; B: SeC structure under scanning electron microscope; C: Selenized chitosan and chitosan Fourier transform infrared spectrum;

[0027] Figure 5This is a schematic diagram of the characterization of SeC@Ru in this invention; AF: Energy dispersive spectroscopy (EDS) elemental distribution of SeC@Ru; G: XRD crystal form of SeC@Ru; IL: XPS diagrams of Ru and Se elements;

[0028] Figure 6 The diagram shows the preparation of SeC@Ru@CS according to the present invention; A: Scanning electron microscope image of SeC@Ru@CS before synthesis; B: Scanning electron microscope image of SeC@Ru@CS after synthesis; C: Fourier transform infrared spectrum of SeC@Ru@CS;

[0029] Figure 7 This is a gross image of the knee joint after modeling and a schematic diagram of HE staining for pathology.

[0030] Figure 8 This is a schematic diagram of chondrocyte culture according to the present invention; 8A: Typical microscopic images of rat chondrocytes isolated from different generations; 8B: Typical toluidine blue staining image;

[0031] Figure 9 This is a representative photograph of the knee joint of rats after 8 weeks of treatment according to the present invention, showing HE staining and Safranin O / Fast Green staining. Detailed Implementation

[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] A chondroitin sulfate-modified selenized chitosan-loaded ruthenium nanozyme comprises a selenized chitosan carrier, a ruthenium nanozyme loaded on the selenized chitosan, and chondroitin sulfate covalently modified onto the surface of the selenized chitosan-loaded ruthenium nanozyme. Chondroitin sulfate is coupled to the amino groups on the selenized chitosan molecular chain via EDC / NHS activation to form amide bonds, yielding the chondroitin sulfate-modified selenized chitosan-loaded ruthenium nanozyme, denoted as SeC@Ru@CS. The ruthenium nanozyme consists of ruthenium nanoparticles with a particle size less than 20 nm, exhibiting catalase-like, superoxide dismutase-like, and peroxidase-like activities. Selenium in the selenized chitosan is grafted onto the amino or hydroxyl groups of the chitosan molecular chain in the form of selenate or selenium heterocycles. Successful grafting of chondroitin sulfate is characterized by a change in the product's zeta potential from positive to negative; and a change in the FT-IR spectrum between 1640 and 1660 nm. An absorption peak of amide I appears at 1540–1560. An absorption peak of amide II was observed at the site; the content of grafted CS was determined by the phenol-sulfuric acid method, the ruthenium loading was determined by ICP-MS, and the selenium content was determined by ultraviolet spectrophotometry or ICP-MS.

[0034] A method for preparing ruthenium nanozymes supported on selenium-modified chitosan with chondroitin sulfate includes the following steps:

[0035] Step 1: Prepare Ruthenium nanozymes RuNPs. Dissolve RuCl3·nH2O and NaAc in ethylene glycol, add PVP, transfer to a polytetrafluoroethylene-lined stainless steel autoclave and heat at 90°C for 12 h. Centrifuge to collect the precipitate, and wash three times with a mixed solvent of 70% ethanol / water to obtain RuNPs suspension.

[0036] Step 2: Prepare selenized chitosan SeC. Chitosan is fully swollen in ultrapure water, glacial acetic acid is added to form a transparent solution, sodium selenite aqueous solution is slowly added, and the reaction is carried out at room temperature for 2 h. Anhydrous ethanol is added to precipitate and wash. The precipitate is pre-frozen at -80℃ and then freeze-dried to obtain selenized chitosan SeC.

[0037] Step 3: Prepare selenized chitosan-supported ruthenium nanozyme SeC@Ru. Add RuNPs suspension to the chitosan solution swollen in step 2, stir thoroughly for 1-2 h, add glacial acetic acid to form a transparent solution, then add sodium selenite aqueous solution and react at room temperature for 2 h. Precipitate with ethanol, wash, pre-freeze at -80℃, and freeze dry to obtain SeC@Ru.

[0038] Step 4: Chondroitin sulfate carboxyl activation. Dissolve chondroitin sulfate (CS) in 0.05 mol / L MES buffer (pH 5.5), add EDC·HCl and NHS, and stir at room temperature for 20–40 min to obtain activated CS solution.

[0039] Step 5: Covalent coupling. SeC@Ru was dispersed in 0.01 mol / L PBS buffer (pH 6.0). The mixture was sonicated for 5–10 min to ensure uniform dispersion. The activated CS solution obtained in Step 4 was slowly added dropwise to the SeC@Ru dispersion. The reaction was carried out at room temperature in the dark for 8–16 h, with the pH controlled at 5.5–6.0 during the reaction. After the reaction was completed, the product was collected by centrifugation, washed with deionized water, dialyzed to remove unreacted substances, and then lyophilized to obtain chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme SeC@Ru@CS.

[0040] Specifically, in steps 2 and 3, the chitosan is medium-viscosity chitosan with a viscosity of 200–400 mPa·s; glacial acetic acid is added at a rate of 1 mL per 50 mL of chitosan aqueous solution; sodium selenite is used at a rate of 1.33 g Na₂SeO₃ dissolved in 1 mL of ultrapure water for every 1 g of chitosan; in step 4, the mass ratio of CS, EDC·HCl, and NHS is 100:76.6:46.0; in step 5, the mass ratio of SeC@Ru to CS is 1:1; the centrifugation conditions in step 5 are 8000–12000 rpm for 10 min, the molecular weight cutoff of the dialysis bag is 8000–14000 Da, the dialysis time is 24 h, and the water is changed every 4 h.

[0041] Example 1: Preparation and characterization of ruthenium nanozymes (RuNPs)

[0042] The RuNPs were prepared using a one-pot solvothermal method. 0.53 g of RuCl3·nH2O and 1.5 g of sodium acetate (NaAc) were dissolved in 15 mL of ethylene glycol, and 569 mg of polyvinylpyrrolidone (PVP) was added. The resulting mixture was transferred to a Teflon-lined stainless steel autoclave and heated at 90 °C for 12 hours. After the reaction was complete, the precipitate was collected by centrifugation at 2314 × g for 5 minutes and washed three times with a 70 vol% ethanol / water mixture to obtain a RuNPs suspension.

[0043] Morphology and particle size: Transmission electron microscopy (TEM) showed that RuNPs were uniformly distributed black small particles with a particle size of less than 10 nm. See [link to TEM]. Figure 1 AC in the context.

[0044] Crystal structure: X-ray diffraction (XRD) patterns show characteristic peaks consistent with standard card PDF#88-1734, confirming a ruthenium crystal structure. See [link to XRD pattern]. Figure 1 D in the middle.

[0045] Valence state: X-ray photoelectron spectroscopy (XPS) shows that the binding energy of Ru 3p3 / 2 is between 461.3 eV and 462.7 eV, confirming that it is a Ru(III) / Ru(II) mixed valence state. See [link to relevant documentation]. Figure 2 EG in the middle.

[0046] Surface potential: Zeta potential measurements show that the RuNPs surface is weakly negatively charged. See [link to relevant documentation]. Figure 1 H in the middle.

[0047] Example 2: Preparation of selenized chitosan (SeC)

[0048] Take 1 g of neutral chitosan with a viscosity of 200-400 mPa·s, dissolve it in 49 mL of ultrapure water, and allow it to swell completely. Use a pipette to add 1 mL of glacial acetic acid to the chitosan solution with vigorous stirring to form a clear solution. Then, dissolve 1.33 g of sodium selenite in 1 mL of ultrapure water and slowly add it dropwise to the above clear solution. React at room temperature for 2 hours. After the reaction is complete, add sufficient anhydrous ethanol to precipitate and wash twice. Discard the supernatant, wrap the precipitate in aluminum foil, pre-freeze it at -80 ℃, and then freeze-dry it to obtain SeC powder.

[0049] Microstructure: Scanning electron microscopy (SEM) showed that pure chitosan exhibited a dense structure, while selenized SeC displayed a loose, porous structure. (See [link to SEM]) Figure 4 AB in the middle.

[0050] Chemical structure: Fourier transform infrared spectroscopy (FT-IR) shows characteristic absorption peaks of selenium-oxygen bonds (Se=O) at the corresponding wavenumbers, indicating that selenium has been successfully grafted onto the chitosan molecular chain. See [link to relevant documentation]. Figure 4 C in the middle.

[0051] Example 3: Preparation of selenized chitosan-supported ruthenium nanozyme (SeC@Ru)

[0052] Take 1 g of neutral chitosan with a viscosity of 200-400 mPa·s, dissolve it in 49 mL of ultrapure water, and allow it to swell completely. Then add 1 mL of the 1 mg / mL RuNPs nanozyme suspension prepared in Example 1, and stir thoroughly for 1 hour. Next, pipette 1 mL of glacial acetic acid and add it to the above solution while stirring vigorously to form a clear solution. Then, dissolve 1.33 g of sodium selenite in 1 mL of ultrapure water and slowly add it dropwise to the above clear solution, and react at room temperature for 2 hours. After the reaction is complete, add sufficient anhydrous ethanol to precipitate and wash twice, discard the supernatant, wrap the precipitate in aluminum foil, pre-freeze it at -80 ℃, and then freeze-dry it to obtain SeC@Ru.

[0053] Example 4: Preparation of chondroitin sulfate-modified selenium-chitosan-supported ruthenium nanozyme (SeC@Ru@CS)

[0054] This embodiment employs a carboxyl activation-amidation coupling method, utilizing the carboxyl group on chondroitin sulfate (CS) to form a stable amide bond with the amino group on selenized chitosan (SeC).

[0055] CS carboxyl activation: Dissolve 100 mg of chondroitin sulfate (CS) in 10 mL of 0.05 mol / L MES buffer (pH 5.5). Stir magnetically at room temperature until fully dissolved. Add 76.6 mg of EDC·HCl and 46.0 mg of NHS to the solution and continue stirring for 30 min to activate the carboxyl group in the CS molecule.

[0056] Coupling reaction: Take another 100 mg of SeC@Ru prepared in Example 3, disperse it in 20 mL of 0.01 mol / L PBS buffer with pH 6.0, and sonicate for 5-10 min to make it uniformly dispersed.

[0057] Covalent bonding: The activated CS solution was slowly added dropwise to the SeC@Ru dispersion, and the reaction was carried out at room temperature in the dark for 12 hours. The pH of the system was controlled between 5.5 and 6.0 during the reaction.

[0058] Post-processing: After the reaction was completed, the product was collected by centrifugation at 10,000 rpm for 10 min and washed three times with deionized water to remove unreacted CS, EDC, NHS, and byproducts. The product was then placed in a dialysis bag with a molecular weight cutoff of 8,000–14,000 Da and dialyzed for 24 h, with water changed every 4 h. Finally, it was lyophilized to obtain chondroitin sulfate covalently modified SeC@Ru@CS.

[0059] Modification effect

[0060] Potential change: Since chondroitin sulfate carries a strongly negatively charged sulfonic acid group, the Zeta potential of the modified SeC@Ru@CS changes from positive to negative, indicating that CS grafting was successful.

[0061] Spectral evidence: FT-IR spectra show that in the 1640-1660 An absorption peak of amide I appears at 1540-1560. The appearance of an absorption peak for amide II at this location confirms the formation of the amide bond. (See [reference needed]). Figure 6 B and C in the middle.

[0062] Example 5: Application of SeC@Ru@CS in the treatment of osteoarthritis

[0063] A rat model of osteoarthritis was induced by anterior cruciate ligament transection combined with medial meniscectomy. Postoperatively, rats received intra-articular injections once a week, while the control group received an equal volume of saline.

[0064] Eight weeks after treatment, the rat knee joints were harvested for histological analysis.

[0065] HE staining results: as follows Figure 8 As shown, the articular cartilage surface in the model group was rough and eroded, and the cartilage layer was thinned; the articular cartilage surface in the SeC@Ru@CS treatment group was relatively smooth and intact, and the chondrocytes were arranged more regularly.

[0066] Safranin O / Fast Green staining results: as shown Figure 9As shown, the model group showed severe loss of proteoglycans (glycosaminoglycans) in the cartilage matrix, resulting in light staining; the treatment group showed a significant increase in safranin O-positive staining areas in the cartilage matrix, indicating increased cartilage matrix synthesis and significant inhibition of cartilage degeneration.

[0067] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme, characterized in that, The invention comprises a selenized chitosan carrier, a ruthenium nanozyme loaded on the selenized chitosan, and chondroitin sulfate covalently modified on the surface of the ruthenium nanozyme loaded on the selenized chitosan. The chondroitin sulfate is coupled to the amino groups on the selenized chitosan molecular chain via amide bonds formed by the carboxyl groups on the molecular chain and the amino groups on the molecular chain of the selenized chitosan through EDC / NHS activation, resulting in a chondroitin sulfate-modified selenized chitosan-loaded ruthenium nanozyme, denoted as SeC@Ru@CS.

2. The chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme according to claim 1, characterized in that, The ruthenium nanozyme consists of ruthenium nanoparticles with a particle size of less than 20 nm, exhibiting catalase-like, superoxide dismutase-like, and peroxidase-like activities; in the selenized chitosan, selenium is grafted onto the amino or hydroxyl groups of the chitosan molecular chain in the form of selenate or selenium heterocycle.

3. The chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme according to claim 1, characterized in that, The successful grafting of chondroitin sulfate was characterized by the following: the product's zeta potential changed from positive to negative due to the shift from a positive potential to a negative potential in the selenized chitosan-loaded ruthenium nanozyme; and the FT-IR spectrum showed a change in zeta potential between 1640 and 1660 nm. An absorption peak of amide I appears at 1540–1560. An absorption peak of amide II was observed at the site; the content of grafted CS was determined by the phenol-sulfuric acid method, the ruthenium loading was determined by ICP-MS, and the selenium content was determined by ultraviolet spectrophotometry or ICP-MS.

4. A method for preparing ruthenium nanozymes supported on selenium-modified chitosan as described in claim 1, characterized in that, Includes the following steps: Step 1: Prepare Ruthenium nanozymes RuNPs. Dissolve RuCl3·nH2O and NaAc in ethylene glycol, add PVP, transfer to a polytetrafluoroethylene-lined stainless steel autoclave and heat at 90°C for 12 h. Centrifuge to collect the precipitate, and wash three times with a mixed solvent of 70% ethanol / water to obtain RuNPs suspension. Step 2: Prepare selenized chitosan SeC. Chitosan is fully swollen in ultrapure water, glacial acetic acid is added to form a transparent solution, sodium selenite aqueous solution is slowly added, and the reaction is carried out at room temperature for 2 h. Anhydrous ethanol is added to precipitate and wash. The precipitate is pre-frozen at -80℃ and then freeze-dried to obtain selenized chitosan SeC. Step 3: Prepare selenized chitosan-supported ruthenium nanozyme SeC@Ru. Add RuNPs suspension to the chitosan solution swollen in step 2, stir thoroughly for 1-2 h, add glacial acetic acid to form a transparent solution, then add sodium selenite aqueous solution and react at room temperature for 2 h. Precipitate with ethanol, wash, pre-freeze at -80℃, and freeze dry to obtain SeC@Ru. Step 4: Chondroitin sulfate carboxyl activation. Dissolve chondroitin sulfate (CS) in MES buffer, add EDC·HCl and NHS, and stir at room temperature for 20-40 min to obtain activated CS solution. Step 5: Covalent coupling. SeC@Ru was dispersed in PBS buffer and sonicated for 5–10 min to ensure uniform dispersion. The activated CS solution obtained in Step 4 was slowly added dropwise to the SeC@Ru dispersion. The reaction was carried out at room temperature in the dark for 8–16 h, with the pH controlled at 5.5–6.0 during the reaction. After the reaction was completed, the product was collected by centrifugation, washed with deionized water, dialyzed to remove unreacted substances, and then lyophilized to obtain chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme SeC@Ru@CS.

5. The method for preparing ruthenium nanozymes supported on selenium-modified chitosan with chondroitin sulfate according to claim 4, characterized in that, The chitosan mentioned in steps 2 and 3 is medium-viscosity chitosan with a viscosity of 200–400 mPa·s; the amount of glacial acetic acid added is 1 mL of glacial acetic acid per 50 mL of chitosan aqueous solution; the amount of sodium selenite is 1.33 g of Na2SeO3 dissolved in 1 mL of ultrapure water for every 1 g of chitosan; the mass ratio of CS, EDC·HCl and NHS in step 4 is 100:76.6:46.0; the mass ratio of SeC@Ru to CS in step 5 is 1:

1.

6. The chondroitin sulfate-modified selenium-chitosan-supported ruthenium nanozyme and its preparation method according to claim 4, characterized in that, In step 5, the centrifugation conditions are 8000-12000 rpm for 10 min, the molecular weight cutoff of the dialysis bag is 8000-14000 Da, the dialysis time is 24 h, and the water is changed every 4 h.

7. The use of the chondroitin sulfate-modified selenized chitosan-supported ruthenium nanozyme as described in claim 1 in the preparation of a drug for treating osteoarthritis or an intra-articular injection formulation, characterized in that, The SeC@Ru@CS was reconstituted in physiological saline or PBS and administered via intra-articular injection to remove reactive oxygen species in the joint cavity, inhibit chondrocyte apoptosis, promote cartilage matrix synthesis, and reduce cartilage damage in osteoarthritis.